Suboptimal infection prevention and control in the healthcare culture - Cioffi, Domenico; Cioffi, Jane (International Journal of Infection Control, 2019)
Healthcare associated infections are one of the most common complications of hospitalised patients althoughthey are largely preventable through compliance with infection prevention and control standards andguidelines. Clinical performance has been associated with culture in health care. By exploring the influence ofculture in health care on infection prevention and control practice, understanding and insight into suboptimalIPC practice may be exposed. This paper discusses the cultural milieu of IPC practice and embedded normsproposing a cultural shift is mandatory to address suboptimal IPC practice. Recommendations are made that acultural shift to blend the cure and prevention paradigms that effectively supports optimal infection preventionand control practice be envisaged by healthcare workers and implemented.